Thermal emission and line profiles from magnetized accretion disks - Ranea Sandoval, Ignacio Francisco (2014)
Observations of X-ray binary systems provide strong evidences of the existence of compact objects too massive to be explained by current neutron star models. When these systems are in the thermal (high/soft) state their emission spectra in the 0.1 − 5 keV range can be modeled by means of the thermal radiation of an accretion disk formed around super-compact objects. The profile of the fluorescent iron line is useful to get insight related with the nature of the compact object. In this work we developed a numerical scheme able to calculate thermal spectra of magnetized Page-Thorne accretion disks formed around both rotating black holes and naked singularities as seen by an arbitrary distant observer. We incorporated two different magnetic field configurations: uniform and dipolar, using a perturbative scheme in the coupling constant between matter and magnetic field. Under the same assumptions we obtained observed synthetic line profiles of the 6.4 keV iron line. We showthat the presence of an externalmagnetic field produces potentially observable modifications on both the thermal energy spectrum and fluorescent iron line profile.